Preoperatively evaluated bladder wall tension as a prognostic parameter for postoperative success after surgery for bladder outlet obstruction - Bross, Stephan; Braun, Peter-Martin; Michel, Maurice Stephan; Martínez y Portillo, Francisco-José; Jünemann, Klaus-Peter; Alken, Peter (Urology, 2003)
Objectives - To evaluate a novel method for the determination of bladder wall tension (BWT) and to correlate these findings with postoperative persistent residual urine, postoperative uroflow, International Prostate Symptom Score, and quality-of-life index in patients with bladder outlet obstruction. - Methods - In 28 male patients with prostate enlargement or bladder neck sclerosis undergoing surgical treatment, the preoperative BWT was determined after urodynamic investigation and ultrasound determination of bladder weight. The patients were divided into two groups: group 1 (n = 24), postoperative residual urine volume less than 50 mL; and group 2 (n = 4), persistent residual urine volume greater than 50 mL. Five patients in group 1 were unobstructed in accordance with the Abrams-Griffiths nomogram. This group was compared separately with group 2, in which all 4 patients were also classified as unobstructed. - Results - The preoperative BWT in group 1 was 5.2 ± 4.1 N/cm2, significantly different from the preoperative BWT in group 2 (0.98 ± 0.3 N/cm2). The BWT in the 5 unobstructed patients in group 1 (3.4 ± 1.3 N/cm2) was significantly greater than that in patients in group 2. BWT was the sole parameter that was distinctly different between these 5 patients and the patients in group 2, with a significant influence on postoperative uroflow, International Prostate Symptom Score, and quality-of-life index. - Conclusions - The results of this pilot study show that the determination of BWT allows further evaluation of the detrusor function. Especially in patients classified as unobstructed according to the Abrams-Griffiths nomogram, preoperative determination of the BWT could become a supplemental and important parameter with predictive value for postoperative success in patients with prostate enlargement or bladder neck sclerosis.
Gesehen am 08.03.2022